Taḥlīlu Al ‘Anāṣiri Al Jāwhārīyati Fī Filmi “Ḍyb” Lī Naji Ābu Nowar (Dirāstun Taḥlīliyyatun Fī ‘Ilmi Al Ādabi) - Indriyati, Reny; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Abstract: The purpose of this study was to determine the intrinsic elements (theme, plot, characterizations, setting, language style) in the film